Menanamkan Nilai-Nilai Pancasila dalam Jiwa Generasi Muda - Aprina Siregar; Martha Traci Simanjuntak; Melina Marbun; Santa Emelia Sitorus; Waliyul Maulana Siregar (Universitas Palangka Raya, 2024)
Pancasila as the ideology and worldview of the Indonesian nation is an important foundation in shaping the character and identity of the younger generation. This study aims to explore efforts to instill Pancasila values in the younger generation and identify supporting and inhibiting factors. The results show that instilling Pancasila values in the psyche of the younger generation requires integrated and sustainable efforts from various parties, namely family, school, community, and media. The family acts as the first environment in instilling Pancasila values through role modeling and daily life practices. Schools have the responsibility to strengthen the understanding and appreciation of Pancasila values through an integrated curriculum and participatory learning methods. The community environment also plays a role in providing space for the younger generation to implement Pancasila values in community activities. Media and technology can be an effective means to instill Pancasila values in the younger generation in a more interesting and contextual way, with proper assistance and control. This study concludes that instilling Pancasila values in the psyche of the younger generation requires a comprehensive approach and active involvement of all stakeholders to ensure the sustainability of the noble values of the Indonesian nation in the future.